Community health workers: a narrative review of a curriculum and training program for low-income communities facing limited access to healthcare - Othman, Maryam; Selnow, Gary W. (Frontiers in Public Health, 2025)
BackgroundThe aim of this narrative review is to examine a WHO-compliant program that prepares Community Health Workers (CHWs) in low-resource environments. The intended outcome of the training is to enhance healthcare access and address health equity disparities. We examined the program’s curriculum, instructional methods, and a complementary continuing medical education (CME) program designed to sustain CHWs’ knowledge and skills.MethodologyWe review, in detail, the CHW training program—its curriculum, delivery, and implementation—launched prior to the COVID-19 pandemic and continuing today. This program develops critical human resources to expand the reach of overburdened healthcare professionals in disproportionately affected regions.ResultsOur review highlights the positive impact of this program on marginalized communities. We propose the adoption of its curriculum and pedagogical framework by local leaders seeking to train teams of well-prepared CHWs to improve healthcare and bridge the gap between communities and medical professionals. This no-cost program is accessible even to the most under-resourced settings.ConclusionThe program examined in this paper offers small, disproportionately affected communities a valuable opportunity to implement a program that equips CHWs to provide essential clinical services and conduct community-wide health education initiatives. These CHWs serve as vital bridges between their communities and the professional medical system. Their demonstrated effectiveness in serving the health needs of their communities, even during the challenging COVID-19 pandemic, is noteworthy. When called for, they can support refugees fleeing war and climate pressures by offering basic clinical care and prevention training.